Monolingual Ideologies vs. Multilingual Realities - Leila Pimentel Lechthoff (PraxisForschungLehrer*innenBildung)
Despite the strive for social justice for and inclusion of recently immigrated students (RIS), the German school system (GSS) is deeply rooted in a monolingual ideology that hinders RIS’ access to equal education. Additionally, monolingual English teaching practices, often paired with the occasional use of German in specific situations, still dominate in ELT classrooms, thus placing RIS who cannot speak either language at a disadvantageous position. The questions of what attitudes ELT teachers articulate towards RIS’ linguistic inclusion, how they assess the role of institutional structures and what would help them to make their classroom more inclusive for RIS is the focus of the research. The core of the study’s data consists of interviews that were conducted with three ELT teachers and evaluated using qualitative content analysis. This article uncovers that the teachers recognize the potential and importance of RIS’ linguistic backgrounds and are sensitive to the needs of RIS. Still, they are not able to accommodate them within their lessons due to the structures of the GSS and teacher education. The article concludes by presenting measures for practices and policies in language education based on the interviewees’ statements that would improve the linguistic inclusion and access to educational opportunities of the increasing body of RIS, ultimately contributing to social justice at German schools.